Influence of antifungal prophylaxis on the occurrence of fungal infections in patients undergoing allogeneic transplantation - Cakic, Jelena; Đunić, Irena (Srpski medicinski časopis Lekarske komore, 2021)
Introduction/Aim: Patients with hematologic malignancies such as acute myeloid leukemia and acute lymphoblastic leukemia (AML / ALL), myelodysplastic syndrome (MDS), and those undergoing allogeneic stem cell transplantation (allo SCT) are at the highest risk of invasive fungal infections (IFI). The most common causative agents are Candida spp. and Aspergillus spp. Among the strategies for preventing of IFIs is the adequate implementation of antifungal prophylaxis recommended by the NCCN (National Comprehensive Cancer Network). The aim of the study was to analyze the occurrence of IFI in these patients, as well as the impact and importance of timely antifungal prophylaxis on their development. Methods: Retrospective study included 42 patients, on average aged 35 years, who underwent allo SCT program from 2017 to 2019y and received antifungal prophylaxis in Clinic of Hematology, UKCS. Based on information obtained from medical histories, databases were formed. Statistical analisis included descriptive statistical methods that were done in SPSS programe. Results: 19 (45.2%) patients had clinical manifestation of oral candidiasis. Invasive pulmonary aspergillosis developed in only 3 (7.1%) patients. There was a statistically significant association between clinically manifest aspergillosis (7.1%) and the presence of antigens (Galactomannan) in these patients (p <0.001). There was also a statistically significant association between clinically manifest aspergillosis and spool weakness [2 (66.6%) vs. 1 (33.3%); p = 0.016]. Conclusion: The use of adequate antifungal prophylaxis significantly reduces the incidence of IFIs in patients undergoing the allo SCT program and this contributes to the reduction of morbidity and mortality. Keywords: antifungal prophylaxis, Micafungin, Posaconazole, prophylaxis efficacy